Illusory Superiority and Schizotypal Personality: Explaining the Discrepancy Between Subjective/Objective Psychopathology - Cohen, Alex S. (Personal Disord, 2014)
An interesting paradox has emerged from the literature regarding schizotypy – defined as the personality organization reflecting a putative liability for schizophrenia-spectrum disorders. Across certain cognitive, emotional, quality of life and other functional variables, individuals with schizotypy report experiencing relatively severe levels of pathology. However, on objective tests of these same variables, individuals with schizotypy perform largely in the healthy range. These subjective impairments are paradoxical in that individuals with schizotypy, typically recruited from undergraduate college populations, should be healthier in virtually every conceivable measure compared to chronic, older outpatients with severe mental illness. The present study evaluated the idea that the subjective deficits associated with schizotypy largely reflect a lack of illusory superiority bias – a normally occurring bias associated with an overestimation of self-reported positive qualities and underestimation of negative qualities compared to others. In the present study, both state – measured using laboratory emotion-induction methods – and trait positive and negative emotion was assessed across self (e.g., “how do you feel at this moment”) and other (e.g., “how do most people feel at this moment”) domains in 39 individuals with self-reported schizotypy and 39 matched controls. Controls demonstrated an illusory superiority effect across both state and trait measures whereas individuals with schizotypy did not. These results were not explained by severity of mental health symptoms. These results suggest that a cognitive bias, or lack thereof, is a marker of schizotypy and a potential target for further research and therapy.